Back to origins: Rediscovering the role of individuals in the Uppsala model - Valdemarin, Stefano (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
For 40 years, the Uppsala model has focused on the internationalization of companies, considering the individual level of analysis as a black box. Recently, the model has been criticized by scholars in that regard, and its authors are consequently introducing micro-level processes in some dimensions. But is it possible to fully integrate the micro-level into the Uppsala model? By developing a systematic literature review, our article aims to open this black box. Along with methodological contributions, we rediscover the role of individuals, show how the model can integrate them, develop a comprehensive micro-foundational approach and suggest future research paths.